2021
DOI: 10.5713/ajas.20.0565
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among bedding materials, bedding bacterial composition and lameness in dairy cows

Abstract: Bedding materials directly contact hooves of dairy cows and they may serve as environmental sources of lameness-associated pathogen. However, the specific composition of bacteria hidden in bedding materials is still not clear. The aim of this study was to detect the bedding material and its bacterial composition on lameness of Holstein heifers. Methods: Forty-eight Holstein heifers with similar body weights were randomly assigned into three groups including sand bedding (SB), concrete floor (CF), and compost b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Trueperella pyogenes is a common summer mastitis pathogen (Ishiyama et al, 2017), and was present in a single sample at high abundance, indicating a potential subclinical IMI. Ornithinimicrobium has been detected previously in milk and bedding microbiome samples (Dean et al, 2021;Li et al, 2021), and was linked to be significantly higher in sand bedding in comparison to other beddings (Ray et al, 2022), which is the type of bedding used in the present study.…”
Section: Bacterial Abundance At the Genus Levelsupporting
confidence: 52%
“…Trueperella pyogenes is a common summer mastitis pathogen (Ishiyama et al, 2017), and was present in a single sample at high abundance, indicating a potential subclinical IMI. Ornithinimicrobium has been detected previously in milk and bedding microbiome samples (Dean et al, 2021;Li et al, 2021), and was linked to be significantly higher in sand bedding in comparison to other beddings (Ray et al, 2022), which is the type of bedding used in the present study.…”
Section: Bacterial Abundance At the Genus Levelsupporting
confidence: 52%
“…Pseudonocardia species are associated with heavy metal pollution in soil and have antifungal properties [64,103,104]. JG30-KF-CM5 denitrifying species are beneficial for tobacco growth in reduced N conditions [105,106]. Rokubacteriales are involved in N respiration [61].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, cattle raised on deep sand bedding or deep recycled manure bedding exhibited fewer hock injuries and hock wear than those raised on rubber mattresses [ 8 , 22 ]. The detection of serum biomarkers of joint injury indicated that cattle hock joint injury on the concrete floor was significantly more severe than that on the deep sand bedding or deep fermented bedding [ 28 ]. Our experiment data revealed that the locomotion score of all the cattle in the SFB group and the DFB group was one until the end of the experiment with no serious hock joint injury observed in all cattle of these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Deep sand or sawdust bedding provides limping cows with a more comfortable environment than conventional rubber bedding, thus prolonging lying time [ 25 , 26 , 27 ]. Concrete floor significantly increased the severity of joint injury in cattle, compared with deep sand bedding or deep compost bedding [ 28 ].…”
Section: Introductionmentioning
confidence: 99%